Identification and analysis of smallholder producers’ constraints: Applications to Tanzania and Uganda - Baker, Derek; Cadilhon, Joseph J.; Ochola, W. (Informa UK Limited, 2015)
This article puts forward a method for the analysis of constraints faced by developing countries’ smallholder producers. It is consistent with theories of constraints, efficient in terms of cost and researchers’ time, and accessible to a non-technical audience. A hybrid of workshop discussion and individual data collection, it also draws on data and analyses available in most developing countries. The article presents an application to smallholder livestock systems in Tanzania and Uganda, reporting results and analysis relating constraints to households’ characteristics and conditions, and their stated goals. While limitations are identified, it is proposed for application in other development fields.